Investigating the Potential of Phosphatidylcholine-Based Nano-Sized Carriers in Boosting the Oto-Topical Delivery of Caroverine: in vitro Characterization, Stability Assessment and ex vivo Transport Studies - Farrah AY (Dove Medical Press, 2020)
Amira Yousry Farrah,1 Abdulaziz M Al-mahallawi,2,3 Emad B Basalious,2 Demiana I Nesseem1 1Department of Pharmaceutics, National Organization for Drug Control and Research, Cairo, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 3Department of Pharmaceutics, Faculty of Pharmacy, October University for Modern Sciences and Arts (MSA), Giza, EgyptCorrespondence: Emad B BasaliousDepartment of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo 11562, EgyptTel +2 01202000454Email emad.basalious@pharma.cu.edu.egPurpose: Drug delivery into the inner ear across the intact tympanic membrane (TM) has been a challenge in the treatment of inner ear disorders. In this study, nano-sized carriers were formulated for improving the non- invasive oto-topical delivery of caroverine for the treatment of tinnitus.Methods: Caroverine was loaded into two types of phospholipid-containing systems, namely, nano elastic vesicles (EVs) and phosphatidylcholine-based liquid crystalline nano-particles (PC-LCNPs). The prepared formulations were characterized for their drug loading, particle size, polydispersity index, zeta potential, morphological features by transmission electron microscopy (TEM), and physicochemical stability. In addition, comparative ex vivo transport study was carried out using rabbits’ TM for both types of formulations.Results: The findings show a significant superiority of PC-LCNPs over the EVs formulations in the drug payload (1% and 0.25%, respectively), physical stability and the efficiency of permeation across rabbits’ TM. The results showed a more than twofold increase in the cumulative drug flux values of PC-LCNPs (699.58 ± 100 μg/cm2) compared to the EVs (250 ± 45 μg/cm2) across the TM.Conclusion: The current study revealed the smart physicochemical properties of PC-LCNPs demonstrating the potential of this carrier as a new attractive candidate for improving the non-invasive oto-topical delivery of caroverine.Keywords: caroverine, nanovesicles, liquid crystals, permeation, tympanic membrane